Design of Organic Crystals: Efficient Optical‐to‐THz Conversion Organic Crystals with Simultaneous Electron Withdrawing and Donating Halogen Substituents (Advanced Optical Materials 2/2018). Issue 2 (22nd January 2018) - Lee, Seung‐Jun; Kang, Bong Joo; Shin, Myeong‐Hoon; Lee, Seung‐Chul; Lee, Seung‐Heon; Jazbinsek, Mojca; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract : As shown by Fabian Rotermund, O‐Pil Kwon and co‐workers in article number1700930, there is a promising way for the molecular design of ionic organic nonlinear optical crystals: control of the space‐filling characteristics by introducing substituents that have simultaneous electron‐withdrawing inductive and electron‐donating resonance effects may lead to the enhancement of macroscopic optical nonlinearity and suppression of phonon vibrations for efficient terahertz wave generation.